Analysis of the Perception of Occupational Accident in Mining and Quarry Sector Towards Safe and Healthy Working Environment - Nur Azlina, Abd Rahman; Muhamad Arifpin, Mansor; Ahmad Rasdan, Ismail (2014)
The occurrence of occupational accidents and incidents are increase in parallel of growth of the industries such as mining and quarry. The main objective of this study is to analyze data on the perception of occupational accident in the mining and quarry sector in Malaysia.